SAFEGUARDING CONSUMER RIGHTS: ENHANCING LEGAL PROTECTION AGAINST UNLABELED FOOD PRODUCTS - Palmawati Tahir; Dwi Andayani Budisetyowati; Ani Purwanti; Evis Garunja (Diponegoro Law Review, 2023)
This article addresses the deficient regulations that fail to prioritize consumer interests, resulting in inadequate consumer rights protection. As a result, an abundance of food products disregards labeling requirements in the community. This research seeks to identify remedies and legal safeguards to protect consumers from the dangers of unlabeled food products. The study uses a normative legal research methodology to focus predominantly on a literature review. The data sources include both primary and secondary legal scholarship. The study's findings indicate that the current legal protection for consumers against unlabeled food products needs to be improved. In addition, the supervision of circulating food products intended to protect consumers has yet to be implemented effectively.